2017
DOI: 10.1186/s12888-017-1296-0
|View full text |Cite
|
Sign up to set email alerts
|

Could a short training intervention modify opinions about mental illness? A case study on French health professionals

Abstract: BackgroundIn France, negative views on schizophrenia are pervasive, even among health professionals. Prior research suggests that the level of prejudice is lower when the illness is described with the example of a specific individual. This finding highlights the importance of designing local, targeted destigmatization campaigns. The present study aims to evaluate the benefits of a short intervention offering contact with psychiatric services users on reducing the stigma about mentally ill people, among a sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
6
0
4
Order By: Relevance
“…In addition to direct social contact with in-person live interactions between people, studies that include filmed interventions, which provide indirect social contact, are also effective at reducing stigma (Clement et al, 2012; Faigin & Stein, 2008). This data is corroborated by the results from two studies included in this review, which led to a reduction in stigma levels among participants (Hawke et al, 2013; Villani and Kovess, 2017).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In addition to direct social contact with in-person live interactions between people, studies that include filmed interventions, which provide indirect social contact, are also effective at reducing stigma (Clement et al, 2012; Faigin & Stein, 2008). This data is corroborated by the results from two studies included in this review, which led to a reduction in stigma levels among participants (Hawke et al, 2013; Villani and Kovess, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…In addition, a film with a character living with mental illness was shown, with the opportunity for discussion after the film. This study highlighted the importance of real narratives from people with lived experience and encouraged the use of appropriate interventions for a specific target group (Villani and Kovess, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the CAMI scale was used to study an anti-stigma campaign in France that measured changes on the opinions about mental illness in French health professionals after receiving a short training intervention program. This study showed no publication of psychometric data ( 14 ). Another recent study validated in French the Stigma scale, which measures perceived stigma.…”
Section: Introductionmentioning
confidence: 67%
“…Mental Health Knowledge Schedule (MAKS) ( 10 ) and the Reported and Intended Behavior Scale (RIBS) ( 11 ) were then developed to assess knowledge and behavior, in order to measure every dimension of stigma as defined by Thornicroft ( 12 ). In previous studies these three scales showed to be sensitive to anti-stigma centered actions ( 13 , 14 ). Further details on these three scales are provided in the Section “ Materials and Methods ” of this article.…”
Section: Introductionmentioning
confidence: 96%
“…The absence of such an education leads to major stigma, and thereby to discrimination, and can represent an obstacle to the implementation of the most human rights-oriented legislations (Freeman et al , 2005). There are examples of training interventions which have succeeded in decreasing stigma among health professionals (Villani and Kovess-Masfety, 2017). A training course on the CRPD and the QualityRights toolkit was organized in Elrazi after this study and showed significant differences in the awareness of rights by the participants before and after the one-week course (Carta et al , 2020).…”
Section: Discussionmentioning
confidence: 99%